2017
DOI: 10.1016/j.bbabio.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of mitophagy in carcinogenesis and tumor progression

Abstract: The mitochondrial role in carcinogenesis and cancer progression is an area of active research, with many unresolved questions. Various aspects of altered mitochondrial function have been implicated in tumorigenesis and tumor progression, including mitochondrial dysfunction, a metabolic switch to aerobic glycolysis, and dysregulation of mitophagy. Mitophagy is a highly specific quality control process which eliminates dysfunctional mitochondria and promotes mitochondrial turnover, and is involved in the adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 95 publications
1
54
0
1
Order By: Relevance
“…We observed that HLA-I/II peptides stemmed mainly from self proteins localized within the endosome-lysosome compartments and were enriched with phagosomal structural proteins and phagosomal cargo proteins that are degraded by autophagy (Figure 2 ). Among them are ribosomal proteins and mitochondrial proteins that may be selectively degraded and eliminated in the processes called ribophagy ( 48 ) and mitophagy ( 49 ), respectively. Previously, we studied HLA-I presentation in several cell lines and we have shown that ribosomes and mitochondrial proteins are presented to a higher extent than what would be expected from their abundance ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that HLA-I/II peptides stemmed mainly from self proteins localized within the endosome-lysosome compartments and were enriched with phagosomal structural proteins and phagosomal cargo proteins that are degraded by autophagy (Figure 2 ). Among them are ribosomal proteins and mitochondrial proteins that may be selectively degraded and eliminated in the processes called ribophagy ( 48 ) and mitophagy ( 49 ), respectively. Previously, we studied HLA-I presentation in several cell lines and we have shown that ribosomes and mitochondrial proteins are presented to a higher extent than what would be expected from their abundance ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies show that BNIP3 has a pro-tumorigenic role; its inactivation reduced cell migration and its upregulation suppressed the mTOR/S6K1 pathway. It is hypothesized that the dual role of BNIP3 can be explained by alternative splicing or variable transcriptional regulation via transcription factor Sp3 ( 111 , 112 ).…”
Section: The Mitochondrial–lysosomal Interplay In Cancermentioning
confidence: 99%
“…Mitophagy, the selective targeting of damaged mitochondria for lysosomal degradation, is an essential process controlling mitochondrial homeostasis. Being at the crossroads of metabolic, redox and cell death pathways, mitochondria play a central role in physiology and, not surprisingly, in several pathological settings, including cancer [1][2][3]. Although dysfunctional mitochondria are a feature of many malignancies, and contribute to the increased glycolytic metabolism referred as "Warburg effect" [4][5][6], it is becoming clear that these organelles may also contribute to tumorigenesis by i) producing signaling molecules [7][8][9]; ii) controlling Ca 2+ homeostasis [10]; iii) acting as hub of cell death signals [11,12]; iv) catabolizing lipids and amino acids for energy production, or v) stimulating their de novo synthesis to generate biomass in proliferating cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although dysfunctional mitochondria are a feature of many malignancies, and contribute to the increased glycolytic metabolism referred as "Warburg effect" [4][5][6], it is becoming clear that these organelles may also contribute to tumorigenesis by i) producing signaling molecules [7][8][9]; ii) controlling Ca 2+ homeostasis [10]; iii) acting as hub of cell death signals [11,12]; iv) catabolizing lipids and amino acids for energy production, or v) stimulating their de novo synthesis to generate biomass in proliferating cells [13,14]. Due to these multiple roles, changes in the mitochondrial mass, which mostly derives from an imbalance between biogenesis and mitophagy, has been linked to both tumorigenesis and cell survival, as well as to tumor suppression [15]. Although mitophagy appears to be defective during cancer initiation, it acts mainly as a cytoprotective mechanism during cancer progression, as it supports cell survival under stressful conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation